A DSL for WSN software components coordination. Issue 98 (May 2021) - Carrero, Marcos Aurélio; Musicante, Martin A.; dos Santos, Aldri Luiz; Hara, Carmem S.
Abstract: Wireless Sensor Networks (WSNs) have become an integral part of urban scenarios. They are usually composed of a large number of devices. Developing systems for such networks is a hard task and often involves validation on simulation environments before deployment on real settings. Component-based development allows systems to be built from reusable, existing components that share a common interface. This paper proposes a domain specific language (DSL) for coordination of WSN software components. The language provides high-level composition primitives to promote a flexible coordination execution flow and interaction between them. We present the language specification as well as a case study of an in-network WSN data storage coordination. The current specification of the language generates code for the NS2 simulation environment. The case study shows that the language implements a flexible development model. Moreover, we analyze the code reusability promoted by the language and show that it reduces the programming effort in a component-based development framework. Highlights: It tackles the problem of developing complex systems for WSNs. A DSL called SLEDS is proposed to develop the orchestration of WSN components. SLEDS closely resembles state machines. SLEDS provides an intuitive approach for WSN software components coordination. A case study shows that SLEDS implements a flexible development model. An analysis of code reuse and reduction of programming effort is presented.